Process improvement approaches within the English NHS: A systematic review - Kerrigan, Matthew. D. (2022)
Abstract Purpose: The objective of this paper is to provide a synthesised, holistic view of process improvement approaches within the English NHS. It aims to find the approaches used, any variations in application, key process improvement tools, common outcomes for approaches, common errors and barriers, and key influences on the sustainability of a project. Design/methodology/approach: The author conducted a systematic literature review of articles relevant to the English NHS in the period of 2020 - July 2022. Based on a total of 151 studies, the author conducted a thematic analysis to identify key themes in use of process improvement approaches and tools, and factors influencing the sustainability of the intervention/programme. Findings: The review found a wide range of process improvement approaches used by actors in the English NHS. Variation was present in the implementation of the approaches; some studies reported local variations of some methodologies. Projects without methodologies tended to be smaller scale quality improvements, and in some cases would have benefitted from the use of a methodology. Additionally, the number of tools also increases with the use of a methodology. The most common impediment to sustainability were organisational factors, such as junior doctor rotations. Research limitations/implications: This dissertation was conducted by a single author. It is also likely influenced by publication bias, and it only covers a small scope and so generalisability to other areas of research is limited. Practical implications: This paper provides valuable insights for both actors within the NHS, and those in academia. It provides a foundation of knowledge regarding the current trends in usage of process improvement approaches. It will also provide future researchers and process improvement projects with the ability to define future implementation needs. Originality/value: The findings are derived from a systematic literature review which has utilised best practice to form its method and the way in which it has been reported. To the author’s knowledge, there are no similar reviews of its type currently published. The review provides a strong foundation to guide future research and process improvement concerning the English NHS. Paper type – Systematic Literature Review